SCIENCE MAPPING BASED ON CO-WORD FOR STUDY OF INDONESIAN LITERATURE ARTICLE IN SCIENTIFIC JOURNAL - Ellya Ratna; Malta Nelisa (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
PEMETAAN BERBASIS CO-WORD UNTUK KAJIAN ARTIKEL SASTRA INDONESIA DALAM JURNAL ILMIAHAbstractStudies in the field of Indonesian literature plays an important role in demonstrating what life style Indonesia's diverse society. From studies that have been done have not seen a picture whether the study of Indonesian literature has evolved over some period of time with the possibility of the emergence of new topics in the study of Indonesian literature. Research conducted with quantitative approach using bibliometric analysis which includes analysis of the subject, co-word analysis, cluster analysis, and multidimensional scalling. Data were collected by identifying the scientific articles in the field of Indonesian literature contained in published scientific journal in Indonesia from 2008—2012 through the Indonesian Scientific Journal Database (ISJD) PDII LIPI. The results of this study indicate the following matters. First, the linkage of subjects in the field of Indonesian literature illustrated by the analysis group produced five cluster group. Each group describes the linkages between topics in a subject. Second, the development of the subject field map Indonesian literature for the years 2008—2012 shows five study groups in literature articles Indonesia, namely literary criticism, folklore, literary theory, history of literature, and philology. Most of the articles discuss various topics of literary theory in the study.Keywords: bibliometric; co-word analysis; multidimensional scalling  Abstrak Kajian di bidang sastra Indonesia berperan penting dalam memperlihatkan corak kehidupan masyarakat Indonesia yang beraneka ragam.Dari kajian-kajian yang telah dilakukan belum terlihat gambaran apakah kajian sastra Indonesia mengalami perkembangan dari beberapa kurun waktu dengan kemungkinan munculnya topik-topik baru dalam kajian sastra Indonesia.Penelitian dilakukan dengan pendekatan kuantitatif menggunakan analisis bibliometrika yang mencakup analisis subjek, analisis co-word, analisis gugus, dan peta multidimensi. Data penelitian dikumpulkan dengan mengidentifikasi artikel-artikel ilmiah di bidang sastra Indonesia yang terdapat dalam jurnal ilmiah yang terbit di Indonesia dari tahun 2008—2012melalui Indonesian Scientific Journal Database (ISJD) PDII LIPI.Hasil penelitian menunjukkan hal-hal sebagai berikut.Pertama, keterkaitan subjek dalam bidang sastra Indonesia digambarkan melalui analisis gugus yang menghasilkan lima kelompok gugus. Setiap gugus menggambarkan keterkaitan diantara topik-topik dalam suatu subjek. Kedua, peta perkembangan subjek bidang sastra Indonesia untuk tahun 2008—2012 memperlihatkan lima kelompok kajian artikel bidang sastra Indonesia, yaitu kritik sastra, folklore, teori sastra, sejarah sastra, dan filologi. Sebagian besar artikel membahas tentang teori sastra dalam berbagai topik kajian.Kata Kunci:bibliometrik; analisis co-word; peta multidimensi; sastra Indonesia